Registration of Religious Organizations - Between Collective and Corporate Right to Religious Freedom - Đukić, Dalibor B (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Abstract: The primary focus of the paper is on the right of religious communities to acquire legal personality. For religious communities this issue has existential importance. Denying access to such status imposes impermissible limitations on freedom of religion or belief. The majority of religious communities seek legal entity status, because it is necessary if they want to acquire property, hire personal, apply for governmental permits etc. The right to acquire legal entity status is one of the most critical arrangements needed for religious liberty in contemporary societies. The paper includes analysis of three important characteristics of this procedure. Access to legal personality for religious or belief communities should be non-mandatory, quick and transparent. It should be taken into account that competent authorities for various political or social reasons, made untimely decisions or refused to register religious organizations due to alleged formal deficiencies. In these cases, the procedures themselves and excessive formalism were used as a mechanism to control the number of recognized religious organizations and to deny the status of a legal entity to certain religious groups. In order to prevent such occurrences, it is necessary to protect the competent authorities from all those influences that prevent them from acting impartially and neutrally. There is a variety of ways that the right to legal personality can be provided for religious communities. Registration system should be compliant with international human rights norms and it is important to recognize that registration is not a primary mechanism for exercising social control of religion.
Keywords: religious organizations, legal personality, freedom of assembly and association, religious freedom.